FUNGSI JURNALISTIK DAN STRATEGI PENULISAN PADA PORTAL LINE TODAY - Ulfa Khairina (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
LINE TODAY is one of various news portal account supported by social media application called LINE. The research conducted the journalism function of LINE TODAY on February 2017 by using content analysis. There are four journalism function, LINE TODAY placed to entertainment more than to inform, to educate or to do social control. The choosen articles by LINE TODAY are the news which using various strategies, that are categorization, identification, individualization and missrepesentation to attract of reader interest. The political news and the local election are the news which did not like by LINE application users.